Do Explicit and Implicit Parental Financial Socialization Influence Students’ Financial Literacy? Evidence from India - Subramanian, Rameshkumar; Arjun, T. P. (Indian Journal of Finance, 2024)
Purpose : The present study investigated how explicit and implicit parental financial socialization influenced students’ financial literacy (FL). Design/Methodology/Approach : Data were collected from 200 PG students at the Central University of Tamil Nadu, India, using a multiple-stage random sampling technique. Multiple linear regression and an artificial neural network (ANN) analysis were used to identify the most important predictors of FL. Findings : The findings showed that implicit parental financial socialization significantly positively impacted students’ FL; whereas, explicit parental financial socialization did not. Additionally, students’ FL is not considerably impacted by viewing parents as financial role models. Still, when parents had more income and educational attainment, their children showed a larger degree of FL. Based on the ANN analysis, implicit parental financial socialization was the most significant predictor of students’ FL. Practical Implications : The findings emphasized that parents must receive adequate financial education and exhibit responsible financial behavior in order to improve students' FL and their financial well-being. Originality : The impact of parental financial socialization, both explicit and implicit, on pupils’ financial literacy in the Indian setting has not, as far as we are aware, been studied in the literature before.